Create diversity and equality in the workplace through inclusive and fair HR management practices - Faruk Faruk (Institute of Computer Science (IOCS), 2024)
This research aims to describe the implementation of inclusive and fair human resource management (HR) practices in realizing diversity and equality in the workplace. The research method used was a descriptive approach with sampling using total population techniques or saturated samples of 105 BUMD employees in the port services sector in East Java. Data was collected using the Diversity Management Climate Scale (DMCS) and the Workplace Inclusion Scale (WIS), and analyzed using descriptive statistical analysis techniques. The research results show the company's commitment to increasing inclusion and fairness in the workplace, but there are still challenges in achieving optimal levels of employee satisfaction. The steps that have been taken are positive steps, but require in-depth evaluation of existing policies and procedures, as well as active employee participation in the improvement process. Through a holistic and sustainable approach, port services BUMD companies in East Java can create a more inclusive and equitable work environment, which will have a positive impact on the company's overall performance and productivity.